Historical development of altitude training and hypoxic conditioning - Wilber, R. L. (Hypoxia conditioning in health, exercise and sport: Principles, mechanisms and applications, 2025)
Contains the historical development of altitude training and hypoxic conditioning, including the living low and training high approach as well as the living high and training low approach. It also contains current issues and trends as well as an outlook into the future.